Variable levels of spike and ORF1ab RNA in post-mortem lung samples of SARS-CoV-2-positive subjects: comparison between ISH and RT-PCR - Zito Marino, Federica; De Cristofaro, Tiziana; Varriale, Massimo; Zannini, Giuseppa; Ronchi, Andrea; La Mantia, Elvira; Campobasso, Carlo Pietro; De Micco, Francesco; Mascolo, Pasquale; Municinò, Maurizio; Municinò, Emilia; Vestini, Francesco; et al. (Virchows Archiv : an international journal of pathology, 2022)
Post-mortem examination plays a pivotal role in understanding the pathobiology of the SARS-CoV-2; thus, the optimization of virus detection on the post-mortem formalin-fixed paraffin-embedded (FFPE) tissue is needed. Different techniques are available for the identification of the SARS-CoV-2, including reverse transcription polymerase chain reaction (RT-PCR), immunohistochemistry (IHC), in situ hybridization (ISH), and electron microscopy. The main goal of this study is to compare ISH versus RT-PCR to detect SARS-CoV-2 on post-mortem lung samples of positive deceased subjects. A total of 27 samples were analyzed by RT-PCR targeting different viral RNA sequences of SARS-CoV-2, including envelope (E), nucleocapsid (N), spike (S), and open reading frame (ORF1ab) genes and ISH targeting S and Orf1ab. All 27 cases showed the N gene amplification, 22 out of 27 the E gene amplification, 26 out of 27 the S gene amplification, and only 6 the ORF1ab gene amplification. The S ISH was positive only in 12 out of 26 cases positive by RT-PCR. The S ISH positive cases with strong and diffuse staining showed a correlation with low values of the number of the amplification cycles by S RT-PCR suggesting that ISH is a sensitive assay mainly in cases carrying high levels of S RNA. In conclusion, our findings demonstrated that ISH assay has lower sensitivity to detect SARS-CoV-2 in FFPE compared to RT-PCR; however, it is able to localize the virus in the cellular context since it preserves the morphology.